State-Society Interaction in Addressing Crisis from the Communication Processes of Resilience Perspective: A Case of Local Government Role in Redeveloping Pandeglang Tourism Business - Siti Dewi Sri Ratna Sari; Djuara P Lubis; Pudji Muljono; Nurmala K Pandjaitan (Sodality: Jurnal Sosiologi Pedesaan, 2024)
Tourism has significantly contributed to Indonesia’s GDP despite being vulnerable to crisis. Pandeglang Regency with its 14 tourism villages is one among regions that expects income from tourism which unfortunately attacked by tsunami crisis in the end of December 2018, aggravated by travel restriction policies during COVID-19 pandemic since end of March 2020. State-society interactions become important in addressing those crises. Through the commmunication processes of resilience perspective, this research aims to analyze the state-society interactions in addressing crisis on a case of local government agency’s role to redevelop Pandeglang Regency tourism business after crisis. This study uses quantitative approach, strengthened by qualitative research. This study applies survey research to 144 owners of Tourism MSMEs with descriptive analysis by SPSS 25.0, supported by analysis of interviews, a focus group discussion and field observations. The research results show that local tourism-related government agencies have a significant role in the state-society interactions addressing the crisis to redevelop Pandeglang tourism business where Pandeglang Regency Tourism Office has the most significant role. However, this agency needs to communicate more evenly to all Tourism MSMEs’ owners. It is also found that the communication processes of resilience perspective have led more reciprocal interactions between the state and the society.